Characterizing mass, momentum, energy, and metal outflow rates of multiphase galactic winds in the FIRE-2 cosmological simulations. Issue 2 (2nd October 2021) - Pandya, Viraj; Fielding, Drummond B; Anglés-Alcázar, Daniel; Somerville, Rachel S; Bryan, Greg L; Hayward, Christopher C; Stern, Jonathan; Kim, Chang-Goo; Quataert, Eliot; Forbes, John C; Faucher-Giguère, Claude-André; Feldmann, Robert; et al.
ABSTRACT: We characterize mass, momentum, energy, and metal outflow rates of multiphase galactic winds in a suite of FIRE-2 cosmological 'zoom-in' simulations from the Feedback in Realistic Environments (FIRE) project. We analyse simulations of low-mass dwarfs, intermediate-mass dwarfs, Milky Way-mass haloes, and high-redshift massive haloes. Consistent with previous work, we find that dwarfs eject about 100 times more gas from their interstellar medium (ISM) than they form in stars, while this mass 'loading factor' drops below one in massive galaxies. Most of the mass is carried by the hot phase (>10 5 K) in massive haloes and the warm phase (10 3 −10 5 K) in dwarfs; cold outflows (<10 3 K) are negligible except in high-redshift dwarfs. Energy, momentum, and metal loading factors from the ISM are of order unity in dwarfs and significantly lower in more massive haloes. Hot outflows have 2−5 × higher specific energy than needed to escape from the gravitational potential of dwarf haloes; indeed, in dwarfs, the mass, momentum, and metal outflow rates increase with radius whereas energy is roughly conserved, indicating swept up halo gas. Burst-averaged mass loading factors tend to be larger during more powerful star formation episodes and when the inner halo is not virialized, but we see effectively no trend with the dense ISM gas fraction. We discuss how our results can guide future controlled numerical experiments that aim to elucidate the key parameters governing galactic winds and the resulting associated preventative feedback.